Performance of Selective Channel Assignment Method in Cognitive Radio System - ZMallikrjuna Gowda C P, Vijayakumar T (International Journal of Advanced Science and Technology, 2020)
In this paper, simulations are run for various models. The models are based on type of channel assignment methods, with and without usage of converters, considering primary unit calls and secondary unit calls separately. Totally eight models are developed as part of this work. Channel assignment methods namely, first fit assignment, uniformly distributed random assignment and selective channel assignment methods are used. The percentage of PU calls are varied from 50% to 75%. Also, each of the models has variant for with conversion and without conversion of wavelength. The simulations are run for a network having 10 channels, 15 links and 8 Erlangs of load. As part of the simulations, the blocking probabilities and throughput are computed. Also, the channel usage frequency is computed for each of the assignment methods.